2023
DOI: 10.1029/2023je007865
|View full text |Cite
|
Sign up to set email alerts
|

On the Diversity and Formation Modes of Martian Minerals

Abstract: A systematic survey of 161 known and postulated minerals originating on Mars points to 20 different mineral‐forming processes (paragenetic modes), which are a subset of formation modes observed on Earth. The earliest martian minerals, as on Earth, were primary phases from mafic igneous rocks and their ultramafic cumulates. Subsequent primary igneous minerals were associated with products of limited fractional crystallization, including alkaline and quartz‐normative lithologies. Significant mineral diversificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 428 publications
0
5
0
Order By: Relevance
“…Secondary minerals predicted by evaporation models in this study have been detected at various Martian sites including Gale crater, Hellas basin, and Marth Vallis (Bristow et al., 2018; Carter et al., 2013; Ehlmann et al., 2009; Hazen et al., 2023; Milliken et al., 2008; Rampe et al., 2017). Amorphous silica and sulfate deposits on the surface of Mars and in Martian meteorites are thought to have been formed following precipitation in cracks and pores during diagenesis or following evaporation of brines (Achilles et al., 2020; Bridges & Grady, 2000; Bristow et al., 2018; Changela & Bridges, 2011; Hazen et al., 2023; Milliken et al., 2008; Rampe, Blake, et al., 2020; Rapin et al., 2019; Vaniman et al., 2018), whereas Fe/Mg clays and zeolites identified by orbiters and/or rovers on Mars are usually considered secondary phases produced by the alteration of basalts in aqueous solutions at ambient and/or hydrothermal temperatures (Achilles et al., 2020; Bishop et al., 2008; Bristow et al., 2015, 2018, 2021; Ehlmann et al., 2009; Kodikara et al., 2023; Milliken et al., 2010; Poulet et al., 2005; Rampe, Blake, et al., 2020; Viviano et al., 2013). However, experimental and field studies have demonstrated that Fe/Mg clays and zeolites can also form by direct precipitation or transformation of precursor minerals in near‐neutral to alkaline waters at ambient temperature (Bristow & Milliken, 2011; English, 2001; Pedro et al., 1978; Tosca et al., 2011).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Secondary minerals predicted by evaporation models in this study have been detected at various Martian sites including Gale crater, Hellas basin, and Marth Vallis (Bristow et al., 2018; Carter et al., 2013; Ehlmann et al., 2009; Hazen et al., 2023; Milliken et al., 2008; Rampe et al., 2017). Amorphous silica and sulfate deposits on the surface of Mars and in Martian meteorites are thought to have been formed following precipitation in cracks and pores during diagenesis or following evaporation of brines (Achilles et al., 2020; Bridges & Grady, 2000; Bristow et al., 2018; Changela & Bridges, 2011; Hazen et al., 2023; Milliken et al., 2008; Rampe, Blake, et al., 2020; Rapin et al., 2019; Vaniman et al., 2018), whereas Fe/Mg clays and zeolites identified by orbiters and/or rovers on Mars are usually considered secondary phases produced by the alteration of basalts in aqueous solutions at ambient and/or hydrothermal temperatures (Achilles et al., 2020; Bishop et al., 2008; Bristow et al., 2015, 2018, 2021; Ehlmann et al., 2009; Kodikara et al., 2023; Milliken et al., 2010; Poulet et al., 2005; Rampe, Blake, et al., 2020; Viviano et al., 2013). However, experimental and field studies have demonstrated that Fe/Mg clays and zeolites can also form by direct precipitation or transformation of precursor minerals in near‐neutral to alkaline waters at ambient temperature (Bristow & Milliken, 2011; English, 2001; Pedro et al., 1978; Tosca et al., 2011).…”
Section: Discussionmentioning
confidence: 58%
“…However, experimental and field studies have demonstrated that Fe/Mg clays and zeolites can also form by direct precipitation or transformation of precursor minerals in near‐neutral to alkaline waters at ambient temperature (Bristow & Milliken, 2011; English, 2001; Pedro et al., 1978; Tosca et al., 2011). Talc‐like clays (talc, kerolite) can form at 25°C by direct precipitation from Mg‐rich alkaline brines with a pH >8.5 (Bristow & Milliken, 2011; Tosca et al., 2011; Tutolo & Tosca, 2018); nontronite can form from a ferrihydrite precursor or as secondary product of the reaction of silica with Fe‐oxides (Pedro et al., 1978), which are common and widespread on Mars (Du et al., 2023; Hazen et al., 2023; Rampe, Blake, et al., 2020); zeolites can crystallize from an authigenic amorphous aluminous smectite in saline Na‐rich brines (English, 2001; Hay & Sheppard, 2001; Langella et al., 2001; Remy & Ferrell, 1989), a scenario that is in agreement with model results in this study that predicted zeolites forming after smectites during evaporation of abiotically evolved fluids (Figure 4). Following these arguments, we suggest that water–basalt interaction may not be the only pathway that led to Fe/Mg clays and zeolites formation in Martian basins and neo‐formation of these minerals following evaporation of alkaline brines should not be entirely ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Mars hosts diverse minerals related to mafic-ultramafic rocks and their alteration, which have been observed either through rover tools or through remote sensing, and to which the scientific community will shortly have access. At least 160 distinct mineral species have been identified on, or are postulated to be on, Mars [155], Detailed microand nano-scale mineralogical study of returned Mars samples after the Mars 2020 mission, ongoing investigations of the Jezero Crater, or future high-res sampling in/around the Nili Fossae region will benefit from targeted modeling results. Key indicator minerals are established for reference in future Mars mission-data reduction, to confirm geologically recent habitability in sampled rocks and related environments on Mars, and to direct follow-on analytical work focused on biomarker detection.…”
Section: Modeled Results In the Context Of Planetary Science Missionsmentioning
confidence: 99%
“…Four generalized microbial metabolic reactions were targeted in this study, as in previous work [150][151][152][153][154][155][156]. The Gibbs Free Energy computation values for each reaction (kJ/mol) were normalized to the number of electrons (e − ) transferred [156]…”
Section: Bioenergetic Computationsmentioning
confidence: 99%
“…Hazen et al [128] summarize what is currently known about the diversity and formation modes of Martian minerals and make comparison with the mineral diversity and mineral formation modes of Earth (e.g., [129,130] and references therein). The Martian data set includes results from both orbital and landed in situ observations and measurements from Martian meteorites.…”
mentioning
confidence: 99%